A Literature Study of Indonesian Tourism Human Resources Development in the Era of Society 5.0 - I Made Darsana; I Made Sudjana (STAI Hubbulwathan Duri, 2022)
Tourism industry is one of the sectors that is badly hit by the covid 19 pandemic. Therefore, after the pandemic disappeared as today, all parties must hand-in-hand make efforts to recover this field. This literature review aims to document the efforts of the Indonesian government in making the tourism industry recover as well as the challenges they faced. Five articles that represent the situation were taken from the national journals. These articles were analyzed using three steps of qualitative analysis, namely data classification, verification, and conclusion drawing. The findings of this study reported that the Indonesian government made some programs to develop human resources in this industry, such as giving suitable training and workshops to the agencies they sent. On the other hand, the challenges are also faced by the government and entrepreneurs, especially when giving directions to the policy they made. This study is expected to give an overview about the efforts made in order to redevelop human resource as a way of reconstructing the tourism industry in Indonesia after the pandemic situation in the era of society 5.0.